Perception Student of Nursing Bachelor with Motivation Continuing Education in Professional Field in Nursing Program STIKES Awal Bros Batam - Mira Agusthia; Rachmawaty M Noer (IJECA (International Journal of Education and Curriculum Application), 2018)
Preception is the one of factors influencing one’s motivation. A  student who has negative preception could make them less motivate, otherwise a student who has positive preception make them more motivate, especially if they are motivated to continue their education on nursing professional development . This program is the program of graduate nursing student and professional in Nurse with attitude, behaviour, and professional abilities, and be able to carry out basic nursing care independently. Nursing Profesional Development Sepcialist is higher education level for nurse who has graduated from nursing education (nursing degree) to become profesion of nurse. the purpose of this program to prepare the nurses develop their knowledge and skills in adult learning principles and nursing career development in each specialities. This purpose of research to describe preception students of nursing with motivation to continue professional education in nursing science programs. types of research used on research in this qualitative research. By using method phenomenological research that is: using method (in depth interview). research participants it consists of 10 students. The results of this research is to identify 3 theme clusters according to the goals: according to the cluster theme perception participant is continue the nurses profession, goal of continuing nurses profession, interested in the nursing profession, motivation to continue the nurses profession, perception of nurses profession. The theme cluster hope is to accomplish grade point and program accomplishment nurse profession. The theme cluster support is family and lectures support. Based on the results of the research it is recommended for the undergraduate nursing student to continue the nurses profession, important to be improved because this matter will to increase quality of nursing services.